Neuroinflammation and acquired traumatic CNS injury: a mini review - Theus, Michelle H. (Frontiers in Neurology, 2024)
Acquired traumatic central nervous system (CNS) injuries, including traumatic brain injury (TBI) and spinal cord injury (SCI), are devastating conditions with limited treatment options.Neuroinflammation plays a pivotal role in secondary damage, making it a prime target for therapeutic intervention. Emerging therapeutic strategies are designed to modulate the inflammatory response, ultimately promoting neuroprotection and neuroregeneration. The use of anti-inflammatory agents has yielded limited support in improving outcomes in patients, creating a critical need to re-envision novel approaches to both quell deleterious inflammatory processes and upend the progressive cycle of neurotoxic inflammation. This demands a comprehensive exploration of individual, age, and sex differences, including the use of advanced imaging techniques, multi-omic profiling, and the expansion of translational studies from rodents to humans. Moreover, a holistic approach that combines pharmacological intervention with multidisciplinary neurorehabilitation is crucial and must include both acute and long-term care for the physical, cognitive, and emotional aspects of recovery. Ongoing research into neuroinflammatory biomarkers could revolutionize our ability to predict, diagnose, and monitor the inflammatory response in real time, allowing for timely adjustments in treatment regimens and facilitating a more precise evaluation of therapeutic efficacy. The management of neuroinflammation in acquired traumatic CNS injuries necessitates a paradigm shift in our approach that includes combining multiple therapeutic modalities and fostering a more comprehensive understanding of the intricate neuroinflammatory processes at play.